PEMBERSIH TANGAN OTOMATIS MENGGUNAKAN SENSOR INFRARED BERBASIS ARDUINO - Trismansyah, Trismansyah; Ilham, Dirja Nur; Kurniadi, Sepri; Sipahutar , Erwinsyah; Oktrison, Oktrison (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
The activity of washing hands is still done manually, especially in public places. Few people also wash their hands using water, soap, and tissue excessively to clean their hands. Therefore, the author created a series of automatic hand sanitizer designs using an Arduino-based infrared sensor consisting of three main parts: a water tap, soap, and dryer. This tool works by detecting the hands to be cleaned using an infrared sensor connected to a supporting device. The design of this tool is made to facilitate hand-washing activities to be more practical and hygienic. Based on the test results, it can be concluded that the device that has been made can work well as expected.